Development of measures to assess listening-related effort and fatigue in daily life among hearing aid users: protocol for a quantitative field trial - Trine Flensborg-Madsen; Andreea Micula; Jeppe Høy Konvalinka Christensen; Dorothea Wendt; Hamish Innes-Brown; Ingrid Johnsrude; Matthew Apps; Torsten Dau (BMJ Open)
Introduction Individuals with hearing loss and hearing aid users report higher levels of listening effort and fatigue in daily life compared with those with normal hearing. However, there is a lack of objective measures to evaluate these experiences in real-world settings. Recent studies have found that higher sound pressure levels (SPL) and lower signal-to-noise ratios (SNR) are linked to increased heart rate and decreased heart rate variability, reflecting the greater effort required to process auditory information. This study aims to establish physiological and acoustic predictors of self-reported listening effort and fatigue in daily life. Additionally, the moderating effects of cognitive abilities, personality traits, stress, fatigue, suprathreshold abilities, noise annoyance, lifestyle and health on the development of listening effort and fatigue will be investigated.Methods and analysis A 4-week field trial will be conducted, in which physiological responses will be continuously recorded using Empatica Embrace Plus wristbands. Ambient acoustics will be captured every 20 s via the participants’ (n=60) personal hearing aids, and the participants will provide self-reported momentary assessments through a mobile app throughout the day. Questionnaires will be used to assess personality traits, fatigue, stress and noise annoyance, and gather relevant background information. Cognitive and suprathreshold abilities will also be evaluated. Associations between physiological responses, ambient acoustics and momentary assessments, as well as the potential influence of participant characteristics, will be analysed using multilevel regression models and time-series analyses.Ethics and dissemination Informed consent will be obtained from all participants. The study has been exempted from ethical application by the Science Ethics Committee for the Capital Region of Denmark (journal no. F-23028367). Results will be presented at conferences and submitted for publication in peer-reviewed journals.